Discovering shock absorbing materials on automobiles bumpers through numerical simulations - Khoo, Ding Jie (Nanyang Technological University, 2020)
Automotive bumpers are crucial components in protecting the occupants and the vehicle. By improving the crashworthiness of a bumper, the number of fatalities and repair costs would be reduced. One method is to enhance the energy absorbing capability. An automotive bumper system’s energy absorbing performance is determined by the choice of materials. One potential material that can absorb impact energy is shear thickening fluids. This material solidifies on impact when a shear strain applied exceeds the material’s critical value. Several studies have shown that shear thickening fluids are capable of absorbing high amounts of impact energy, but they have yet to be applied to automotive vehicles. Hence, this study aims to find out if shear thickening fluids can enhance the energy absorbing performance of an automotive bumper. Finite element method will be used to model the automotive bumper to study the behavior and performance. Due to limited amount of resources, the designed model was validated with another similar study that has verified their simulation model with experimental results. The dynamic behavior and energy absorption ratio of the bumper system were calculated and analyzed. The performance of shear thickening fluid materials incorporated into the bumper system was discussed and evaluated.